(untitled) (Triwikrama: Jurnal Ilmu Sosial, 2025)
The Indonesian Plantation Museum 2 (Musperin II) in Medan faces various challenges in carrying out its role as an institution for preserving and educating the history of the national plantation industry, especially due to limited manpower and supporting facilities. This study aims to analyze the role of Musperin II in preserving history, providing education, and managing its collections. The method used is qualitative research with an observational approach, including direct observation in the field and in-depth interviews with museum managers as the main data sources. The results of the study show that Musperin II has succeeded in combining historical narratives with original artifacts, colonial-style architecture, and educational presentations that provide context to Indonesia’s agrarian history. These findings indicate that Musperin II has great potential to develop into a more interactive and technology-based educational institution, so that it can reach the younger generation while strengthening the collective memory and cultural identity of the nation.